1977
DOI: 10.1289/ehp.771911
|View full text |Cite
|
Sign up to set email alerts
|

Questions concerning environmental mobility of arsenic: needs for a chemical data base and means for speciation of trace organoarsenicals.

Abstract: Biomethylation of metals, including arsenic, apparently occurs as a global process. Health control strategies therefore depend on accurate analysis of arsenic's environmental mobility. Determining to what extent biotransformations occur and how resultant organometal(loids) are sequestered in food chains requires sophistication beyond present-day total element determinations. Rather, active molecular forms of arsenic must be speciated for each environmental compartment, and it is necessary to quantify the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 42 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…It has been suggested that increased utilization 55 of compounds containing cadmium has accelerated the rates of mobilization and transport of Cd which far exceed the rates of the natural, abiotic cycling processes (114). These rates have led to increased deposition of cadmium in atmospheric, aquatic and terrestrial environments with subsequent increased uptake of Cd by accumulation in the biota (114).…”
Section: Cadmiummentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that increased utilization 55 of compounds containing cadmium has accelerated the rates of mobilization and transport of Cd which far exceed the rates of the natural, abiotic cycling processes (114). These rates have led to increased deposition of cadmium in atmospheric, aquatic and terrestrial environments with subsequent increased uptake of Cd by accumulation in the biota (114).…”
Section: Cadmiummentioning
confidence: 99%
“…It is generally acknowledged that it is difficult to quantitate the degree of transport of arsenic due to complex multimedia (e.g., sediment/soil-water-biotaair) exchange of arsenic and the natural differences between air, soil, and water systems (55,57). Cycling of arsenic in the environment is dominated by adsorption and desorption to soils and sediments, and is maintained at low concentrations in water and air (57).…”
mentioning
confidence: 99%
See 1 more Smart Citation